Cerastes cerastes snakebite complicated by coagulopathy and cardiotoxicity with electrocardiographic changes. (December 2020) - Razok, Almurtada; Shams, Abdullah; Yousaf, Zohaib
Abstract: Snakebites occur worldwide with varying frequency. Outcomes associated with snakebite are varied and depend on the type of snake and the general health of the patient. We report a case of snakebite by Cerastes cerastes or desert horned viper. Consumptive coagulopathy and cardiotoxicity with electrocardiographic changes complicated the clinical course of the patient. To the best of our knowledge, this is the first reported case in the state of Qatar. Highlights: Healthcare workers should be familiar with the complications of snakebites. Envenomation due to Cerastes cerastes can lead to coagulopathy. Cerastes cerastes envenomation has the potential to cause cardiotoxicity with electrocardiographic changes. Timely administration of antivenom can reverse the systemic effects of envenomation.